Sudden Transition of Pharmacy Education from Traditional to Distance Learning in the Era of COVID-19: Action Steps of a Leading Pharmacy School in Iraq - Ahmed, Kawther K.; Salman, Salema S.; A. Abbas, Wafaa; Alkaisy, Shahad W.; Kathem, Sarmed H. (Iraqi Journal of Pharmaceutical Sciences, 2020)
Education around the world has been negatively affected by the new coronavirus disease (COVID-19) pandemic. Many institutions had to transition to distance learning in compliance with the enforced safety measures. Distance learning might work well for settings with stable internet connections, professional technical teams, and basic implementation of technology in education. In contrast, distance learning faces serious challenges in less fortunate settings with inferior infrastructure. This report aims to shed light on the immediate action steps taken at a leading pharmacy school in Iraq to accommodate for the enforced changes in pharmacy education. The University of Baghdad College of Pharmacy went from less than minimal technology implementation to full distance learning in a remarkable time frame. Pharmacy students were able to finish academic year requirements and move on with the program. Final year students will graduate on time as competent pharmacists.